Śuri et al: A 'chthonic' Etruscan face of Apollon? - Sekita, K (Routledge, 2019)
Aplu, although well-attested on Etruscan mirrors, where his representations are accompanied by inscriptions, occurs in only seven cult inscriptions. The form suris seems to be most frequently attested in the southern sanctuary of Pyrgi. Another great concentration of finds bearing words associated by Colonna with the mysterious Suri comes from Volsini. Thuillier’s proposal to understand suris as the Etruscan equivalent of the Latin sors fails when juxtaposed with the fact that two of the six firm attestations of suris are inscribed on travertine and tufo blocks, which would make them hard to use as sortes. It has long been accepted that Suri, seen as the Etruscan ‘chthonic’ Apollon attested also by a single Greek inscription from the sanctuary as Kore; in the sanctuary there were also found Greek inscriptions possibly referring to Demeter. In Vulci s uris occurs on a tufo block from the fourth century BC.